GBA and APOE Impact Cognitive Decline in Parkinson's Disease: A 10‐Year Population‐Based Study. Issue 5 (2nd February 2022) - Szwedo, Aleksandra A.; Dalen, Ingvild; Pedersen, Kenn Freddy; Camacho, Marta; Bäckström, David; Forsgren, Lars; Tzoulis, Charalampos; Winder‐Rhodes, Sophie; Hudson, Gavin; Liu, Ganqiang; Scherzer, Clemens R.; Lawson, Rachael A.; et al.
Abstract: Background: Common genetic variance in apolipoprotein E ( APOE ), β‐glucocerebrosidase ( GBA ), microtubule‐associated protein tau ( MAPT ), and α‐synuclein ( SNCA ) has been linked to cognitive decline in Parkinson's disease (PD), although studies have yielded mixed results. Objectives: To evaluate the effect of genetic variants in APOE, GBA, MAPT, and SNCA on cognitive decline and risk of dementia in a pooled analysis of six longitudinal, non‐selective, population‐based cohorts of newly diagnosed PD patients. Methods: 1002 PD patients, followed for up to 10 years (median 7.2 years), were genotyped for at least one of APOE ‐ε4, GBA mutations, MAPT H1/H2, or SNCA rs356219. We evaluated the effect of genotype on the rate of cognitive decline (Mini‐Mental State Examanation, MMSE) using linear mixed models and the development of dementia (diagnosed using standardized criteria) using Cox regression; multiple comparisons were accounted for using Benjamini−Hochberg corrections. Results: Carriers of APOE ‐ε4 (n = 281, 29.7%) and GBA mutations (n = 100, 10.3%) had faster cognitive decline and were at higher risk of progression to dementia ( APOE ‐ε4, HR 3.57, P < 0.001; GBA mutations, HR 1.76, P = 0.001) than non‐carriers. The risk of cognitive decline and dementia (HR 5.19, P < 0.001) was further increased in carriers of both risk genotypes (n = 23). No significant effects were observed for MAPT or SNCA rs356219. Conclusions: GBA and APOE genotyping could improve the prediction of cognitive decline in PD, which is important to inform the clinical trial selection and potentially to enable personalized treatment © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society